Apparent digestibility of protein, energy, and amino acids in some selected feed ingredients for pacu Piaractus mesopotamicus - Abimorad, Eduardo Gianini [UNESP]; Squassoni, G. H. [UNESP]; Carneiro, D. J. (Wiley-Blackwell, 2008)
The apparent digestibility coefficients (ADCs) of amino acids (AA), protein, and energy in six feed ingredients (Brazilian fish meal, soybean meal, corn gluten meal, alcoholic yeast, corn, and wheat bran) we evaluated for pacu juveniles. In general, all ingredients showed high digestibility values for all AA, and differences among ADCs of individual amino acid were detected (P < 0.01). Corn gluten, soybean, and fish meals had the highest ADCs of AA. The ADCs of protein in fish meal, yeast, and corn gluten meal should not be used as AA digestibility indicators, because those showed differences up to 6.7% between the ADCs of protein and AA. All ingredients had lower ADCs of energy than corn gluten meal (P < 0.01). Lysine was the first limiting amino acid in fish meal, corn gluten meal, wheat bran, and corn, and the second limiting amino acid in soybean meal, as methionine was the first limiting amino acid in soybean meal and yeast. However, the soybean meal was the best quality protein source, as it had the highest digestible essential amino acid index. This demonstrated that digestible amino acid values can be used to formulate practical diets for pacu, preventing potential deficiencies or excess that might cause environmental and economic losses.
Keywords: chemical score; digestible amino acids; feed ingredients; Piaractus mesopotamicus; protein quality